(untitled) (Revista de Crítica Literaria Latinoamericana, 2010)
This article presents a reading of two novels by Roberto Bolaño (1953-2003), Distant Star (1996) and Night in Chile (2000) that aims to describe and analyze some procedures to respond to the problem of the limits of language when representing the horror of history in the context of post-dictatorship Latin America. In this sense, the article revolves around the difficulty that arises in relation to the possibilities of verbal art to articulate an account of the past not to shirk its ominous dimension. The article departs from the analysis of the voices that tell the stories of the horrors of Pinochet’s dictatorship during the turbulent seventies.